Approaches to Arabic linguistics : presented to Kees Versteegh on the occasion of his sixtieth birthday - Ditters, Everhard.; Motzki, Harald.; Versteegh, C. H. M. (Studies in Semitic languages and linguistics ;, 2007)
For a lifetime Kees Versteegh played a leading role in Arabic linguistics, dialects (diglossia, creolization, pidginization), the history of Arabic grammar, and other fields related to Arabic. From among his global contacts, colleagues contributed to a Liber Amicorum in appreciation of his stimulating efforts to reopen, deepen and complete our knowledge of Arabic Grammar and Linguistics. In three sections, History, Linguistics and Dialects, 27 contributors discuss (alphabetically): bilingual verb construction; contractual language; current developments; language description; language use; lexicology; organization of language; pause; sentence types; and specific topics: ʾallaḏī; featuring; government; homonymy; ʾiḍmār; inflection; maṣdar; the origin of grammatical tradition; variety conflicts; and verbal schematic (ir)regularities; waqf; and ẓarf.